STRATEGI PEMASARAN USAHA PETERNAKAN CV BERKAH ETAWA DI SANGATTA - Nelly, Nelly (CAM JOURNAL, Jurnal Agen Perubahan Manajemen, 2019)
The purpose of this research  was to find out the right marketing strategy on CV Berkah Etawa. Meanwhile, the implications of this study in the future, expected to be used as a guide for companies in making policy decisions on marketing strategies to increase the sales. The method of this research is qualitative research that uses research procedures that produce data in the form of descriptive speech or writing and the behavior of the object itself. The analytical instrument used is the SWOT method (Strength, Weakness, Opportunity, Threats). The results of this research concluded that internal and external factors along with the cartesius diagram showed that CV Berkah Etawa was still a newly developed company (Growth). The strategy that can be used by CV Berkah Etawa in marketing in order to increase sales is to maintain product quality and quantity, for providing competitive prices and discounted prices for large quantities of purchases), for improving service quality, and for improving the promotion of products offered. Key Note :Marketing Strategy  of Livestock Business CV Berkah Etawa   in Sangatta